The Effectiveness of the Role Playing Method on Students' Speaking Skills in Indonesian Language Learning for Elementary Students - Citra Putri Rosdiana (Institut Agama Islam Negeri Palopo, 2023)
This study aims to improve students' speaking skills through learning with the role play method in grade IV elementary school students in the 2022/2023 school year. Previously, students were still passive in participating in the learning process, especially in Indonesian language subjects because in learning activities the teacher had not used a learning model. Teachers often use the lecture method followed by doing questions in the theme book so that students get bored quickly. The subjects of this study were fourth grade students as an experimental class totaling 28 students. This research is a quantitative research with the form of one pretest-posttest design. This design has a pretest, before treatment and posttest after treatment.